2004
DOI: 10.1254/jphs.fp0030423
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Halothane-Adrenaline Arrhythmia Model Using In Vivo Guinea Pigs

Abstract: Abstract. In vivo antiarrhythmic effects of diltiazem hydrochloride and nifekalant hydrochloride, a pure class III antiarrhythmic drug (Vaughan Williams' classification), on adrenaline induced ventricular arrhythmias were examined in halothane anesthetized guinea pigs. Continuous adrenaline infusion (12.5 m g / kg per min) induced ventricular arrhythmias. Arrhythmogenicity was significantly increased with vagotomy and higher concentration of halothane. After injection of diltiazem at 0.5 mg / kg, the arrhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the present study, we assessed the utility of halothane‐anaesthetized guinea‐pigs as an in vivo model for predicting the QT interval prolongation by new drugs, since guinea‐pigs are less expensive than dogs and are preferable when only a limited amount of drug is available. Guinea‐pigs have been widely utilized for assessing the electropharmacological effects of cardiac ion channel modulators ( Takahara et al ., 1999 ; Noda & Hashimoto, 2004 ). In order to precisely analyse the effects of a drug on the repolarization process of the heart, we first recorded the monophasic action potentials (MAPs) before and after administration of a representative I Kr blocker D ‐sotalol ( Campbell, 1987 ; McComb et al ., 1987 ), under electrical ventricular pacing of various cycle lengths ( Sugiyama & Hashimoto, 2002 ; Sugiyama et al ., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we assessed the utility of halothane‐anaesthetized guinea‐pigs as an in vivo model for predicting the QT interval prolongation by new drugs, since guinea‐pigs are less expensive than dogs and are preferable when only a limited amount of drug is available. Guinea‐pigs have been widely utilized for assessing the electropharmacological effects of cardiac ion channel modulators ( Takahara et al ., 1999 ; Noda & Hashimoto, 2004 ). In order to precisely analyse the effects of a drug on the repolarization process of the heart, we first recorded the monophasic action potentials (MAPs) before and after administration of a representative I Kr blocker D ‐sotalol ( Campbell, 1987 ; McComb et al ., 1987 ), under electrical ventricular pacing of various cycle lengths ( Sugiyama & Hashimoto, 2002 ; Sugiyama et al ., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the guinea pig ventricle lacks I to , the guinea pig has been suggested as a useful animal model for the detection of prolonged QT intervals and drug-induced proarrhythmia liability [6,9,18]. One of the advantages of using a telemetry system for QT evaluation is the possibility of recording the ECG continuously over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we could examine the effects of drugs on the function of the autonomic nervous system. It has been reported that sympathetic/parasympathetic activity modulates the QT interval and ventricular arrhythmia susceptibility [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the guinea pig, under intraperitoneal thiopental anesthesia, intubation was performed to inhale halothane, but due to its small size the atrial electrodes were not used (73). For determining canine effective drug plasma concentrations, continuously occurring adrenaline arrhythmia was produced by intravenous infusion of adrenaline, adjusting the infusion speed enough to produce stable VT lasting about 20 min, but not producing VF (74).…”
Section: -3-2 Methodsmentioning
confidence: 99%